2021
DOI: 10.4018/jgim.20211101.oa39
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dual-Level Transformational Leadership on New Firm Performance

Abstract: In recent years, entrepreneurial bricolage acts as an effective way to solve the problem of resource constraint in new firms, and then gradually attracted attention from related scholars in entrepreneurship field. However, the existing literatures have an obviously insufficient of the implementation and driving factor of entrepreneurial bricolage behavior. Therefore, in this paper, we integrate entrepreneurial bricolage theory with transformational leadership theory to construct a theory model among dual-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 101 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the positive association of PL-SP was consistent with earlier studies. Zhang et al (2021) argue that mono leadership style is insufficient in the complex manufacturing setting, stressing a mixture of diverse leadership styles that provides flexibility to rapid-evolving environments. PL fill this demand by combining two leadership styles (Zhang et al , 2015) and creating a synergy in the organisation to promote sustainability (Gebert et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the positive association of PL-SP was consistent with earlier studies. Zhang et al (2021) argue that mono leadership style is insufficient in the complex manufacturing setting, stressing a mixture of diverse leadership styles that provides flexibility to rapid-evolving environments. PL fill this demand by combining two leadership styles (Zhang et al , 2015) and creating a synergy in the organisation to promote sustainability (Gebert et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturing firms have witnessed incredible transformations during the past century (Del Giudice et al , 2021). The firm’s prime objectives are expanding production scale, lowering costs and enhancing product quality (Zhang et al , 2021). To achieve the organisational goal, firms simultaneously focus on resource maximisation while increasing productivity and efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating blockchain technology into existing enterprise environments can improve the security of enterprise Internet of Things (IoT) information, resist IoT attacks, and play a maintenance role (Stodt et al, 2021). Using blockchain as homomorphic encryption technology for distributed databases can ensure the security of databases, achieve a triple combination of high security, high transparency, and high efficiency, and contribute to improving cost-effectiveness (Ali et al, 2022) (Zhang et al, 2021A).…”
Section: Btmentioning
confidence: 99%
“…Recent studies on FP have found that leadership really matters to FP (Ali & Tang, 2016; Jing et al, 2019; Para-González et al, 2018; D. Wang et al, 2015; Zhang, Bao, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%